On the issue of classification of Mallory-Weiss syndrome - Khakimov M.Sh; Sattarov O.T; Ashurov Sh.E; Ashuraliev Sh.Kh (Genius Journals, 2024)
The aim of the study was to improve the treatment outcomes of patients with MalloryWeiss syndrome by systematizing the clinical signs of the disease and a differentiated approach to the choice of treatment method
Keywords: Mallory-Weiss syndrome; hemostatic therapy; infusion program